PERILAKU ORGANISASI DAN KEPEMIMPINAN SEBAGAI SEBUAH SISTEM - FITRI Fitri (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract: In the last decade Islamic educational institutions have evolved as an increasingly complex institution that requires a well-ordered organization. The complexity of Islamic educational institutions is particularly evident from the need for management of educational implementation by management approach. That is the need to use management science approach in educational institutions especially Islamic educational institutions to be absolute. So the development of educational administration becomes an interesting part for practitioners and educational experts until now. In educational institutions, the relationships between leadership, management, administration and organization are mutually demanding and have an important role in advancing Islamic education institutions. Therefore, these four components can not be separated in educational institutions. Kata Kunci: Organizational Behavior and Leadership